Методичні засади вибору пріоритетних напрямів інноваційного розвитку в Україні - Яковлєв, Анатолій Іванович (Інститут досліджень науково-технічного потенціалу та історії науки ім. Г. М. Доброва НАН України, 2013)
Проаналізовано існуючі методи вибору пріоритетних сфер інноваційного розвитку. Запропоновано методичний підхід, який полягає у визначенні ефекту інновацій при створенні нових робочих місць. На цій основі виявлено пріоритетні галузі для вкладання інновацій, які в найбільшій мірі сприятимуть зростанню економіки держави. Наведено відповідні практичні розрахунки.

A detailed review of existing methods for selecting priority fields of the innovation-driven development in Ukraine is given. A new methodology is proposed, constructed on the assumption that the effect from created new jobs occurs at the three levels: business enterprises (growing effect from recruitment of new employees), population (growing income from earnings), and government (increasing returns of salary tax and VAT, increasing household consumption resulting from increasing household incomes). Calculations are made using official statistical data for 2010. The methodology is tested on the three objects: national economy, agricultural sector, industrial sector. As the largest share of income in Ukraine originates from the industrial sector, it is taken for more detailed analysis by selecting three industries: extracting industry, mechanical engineering, food and beverages. The methodology and related recommendations can be used for better substantiation of priority setting in Ukraine.
Methodological Framework for Selecting Priority Fields of the Innovation-Driven Development in Ukraine
Keywords: інновації; інноваційна діяльність; інноваційні робочі місця; конкурентоздатність інновацій